Mathnawi-yi Haft awrang. Volume 2 : Yūsuf wa-Sulaykhā, Laylā wa-Majnūn, wa-Khiradnāma-yi Iskandar - Jāmī, ʿAbd al-Raḥmān, (Miras Maktoob, ISBN: 9789004365452., 2019)
Regarded by many as the last great mystical poet of medieval Persia, ʿAbd al-Raḥmān Jāmī (d. 898/1492) spent the greater part of his life in Herat. As a student, he excelled in every subject he engaged in and appeared destined for an academic career. But then, in his early thirties, he went through a spiritual crisis that ended in him joining the Herat branch of the mystical Naqshbandiyya order, led by the charismatic Saʿd al-Dīn Kāshgharī (d. 860/1456). A protégé of three successive Timurid rulers in Herat, Jāmī's wide network of friendships and relations extended from spiritual and literary circles through the political to the academic. With 39.000 lines of verse and over 30 prose works to his name, Jāmī's literary production is quite overwhelming. Highly imaginative in their treatment of the human condition, Jāmī's seven long mathnawī s contained in the present two-volume edition bear witness to his great artistic talents and wide intellectual horizon. 2 vols; volume 2.